2012
DOI: 10.1111/j.1445-2197.2012.06168.x
|View full text |Cite
|
Sign up to set email alerts
|

Appendicectomy at a children's hospital: what has changed over a decade?

Abstract: Our institution has experienced an extraordinary rise in the number of appendicectomies performed, which cannot be explained by an increase in the local paediatric population alone. There appears to have been dramatic shift in the surgical care of children to our tertiary paediatric centre. The majority of appendicectomies in 2009 were laparoscopic, with a reduced length of stay despite longer operative times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
0
14
1
Order By: Relevance
“…69 Laparoscopy in Australian children increased from <1% in 1999 to 70% in 2009. 70 Although the 2012 data from the National Survey of Research Commercialization in the United Kingdom demonstrated somewhat lower rates of laparoscopy for appendicitis (60%), this population included adults and nontertiary sites, and some centers did not offer laparoscopy after hours or on weekends. 71 A recent Cochrane review, and a pediatric-focused literature review, recommended that the laparoscopic approach be used unless there is a contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…69 Laparoscopy in Australian children increased from <1% in 1999 to 70% in 2009. 70 Although the 2012 data from the National Survey of Research Commercialization in the United Kingdom demonstrated somewhat lower rates of laparoscopy for appendicitis (60%), this population included adults and nontertiary sites, and some centers did not offer laparoscopy after hours or on weekends. 71 A recent Cochrane review, and a pediatric-focused literature review, recommended that the laparoscopic approach be used unless there is a contraindication.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have important implications for managing emergency surgery for children. During the middle of the first decade of this century, children in NSW with non‐complex emergency surgical conditions, such as appendicitis, were often transferred from metropolitan general hospitals to tertiary paediatric hospitals 16 , 17 . In response to this problem, a statewide paediatric surgery framework was proposed in 2008 18 and adopted in 2014 19 .…”
Section: Discussionmentioning
confidence: 99%
“…During the middle of the first decade of this century, children in NSW with non-complex emergency surgical conditions, such as appendicitis, were often transferred from metropolitan general hospitals to tertiary paediatric hospitals. 16,17 In response to this problem, a statewide paediatric surgery framework was proposed in 2008 18 and adopted in 2014. 19 The framework aimed to facilitate the care of children with noncomplex emergency surgical conditions at metropolitan general hospitals, reducing waiting times, delays in appropriate care, and unnecessary travel or hospital transfers for the families of children who required an appendicectomy.…”
Section: Discussionmentioning
confidence: 99%
“…These may involve missed diagnosis at birth, delays in follow-up by parents, missed diagnosis or lack of timely referral by general practitioners, or limited availability of hospital resources to conduct surgery. 32,33 Missed diagnosis at birth may have occurred because infants were not examined or UDT was missed owing to a lack of experience or training of maternity care providers. Previous studies reveal that when examination is performed by trained experts, the prevalence of UDT detected at birth is higher, as reported in cohorts from Denmark (9%) 2 and Lithuania (5.4%), 34 compared with the 2.1% reported here.…”
Section: Figurementioning
confidence: 99%